Disorder effects produced by the Mn and H incorporations on the optical absorption edge of Ga1-xMnxAs:H nanocrystalline films - Pereira, Andre L. J. [UNESP]; Silva, José Humberto Dias da [UNESP] (Elsevier B.V., 2008)
The optical absorption edges of nanocrystalline Ga1-xMnxAs:H films (0.000 <= x <= 0.081) prepared by sputtering were analyzed. The influence of Mn and hydrogen incorporations were both investigated. The energy dispersive X-ray spectroscopy and X-ray diffraction measurements show that the films are nanocrystalline and do not display any evidence of Mn segregation, or of any other secondary phase formation. The transmittance measurements in the ultraviolet-visible-near infrared range allow us to calculate the absorption coefficient, the optical gap, and the Urbach energy. The hydrogenated Ga1-xMnxAs films presented wider gaps and smaller Urbach energies than its non-hydrogenated counterparts. In the hydrogenated films a linear correlation was observed between the decrease of the optical gap and the increase of the Urbach energy, which we have attributed to potential fluctuations and disorder induced by the Mn incorporation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Amorphous semiconductors; III-V semiconductors; Crystallization; Nanocrystals; Films and coatings; Sputtering; Microstructure; Microcrystallinity; Optical properties; Absorption